TALFIQ DALAM PELAKSANAAN IBADAH DALAM PERSPEKTIF EMPAT MADZHAB - Rasyida Arsjad (CENDEKIA: Jurnal Studi Keislaman, 2015)
This scientific paper is a result of literature research on talfiq in the implementation of the four mazhabs in the turots, especially, presented by scholars of the four mazhab (Shafi'i, Hanafi, Maliki and Hanbali). Talfiq in the implementation of worship is one of the phenomena that often occur in our daily lives, especially in the implementation of worship and muamalah among human beings. The Issues concerning the permissibility of talfiq can occur in dzhaniyah case, not the the obvious and definitive one according to islamic law. it is forbidden as well for some ones doing it by reason tala'ub (playful) and deliberately take the opinion that is light because of solely following their own lusts. So, the conclusion is that as a servant let us always strive to examine and explore the validity of the law in the Shari'ah through texts or sunnah or by asking someone who is an expert in his field of science.